Social Studies Resource Pack Class 1 - The City School (Lahore : The City School)
social studies offer a comprehensive collection of materials designed to enhance students' understanding of their community, culture, and the world. It includes lesson plans, activities, and resources that encourage critical thinking about social issues, geography, history, and citizenship. The pack aims to foster engagement and discussion among students, helping them connect with their environment and develop a sense of responsibility towards their community.
Location: 1B
Keywords: Textbook